COLLAGEN SUPPLEMENTATION AND TISSUE HEALTH IN MIDDLE-AGED AND OLDER ADULTS: A NARRATIVE REVIEW OF CLINICAL EVIDENCE - Aleksandra Maria Błoch; Natalia Rządzińska; Kornelia Julia Fimiarz; Aleksandra Olga Pakulska; Maria Anna Miller; Aleksandra Jolanta Kamińska; Aleksandra Katarzyna Kłosowicz (Archiv Euromedica, 2026)
Background Collagen is the principal structural protein of connective tissues, including the skin, cartilage, tendons, bone, and blood vessels. Ageing is associated with changes in collagen synthesis, organisation, cross-linking, and degradation, which contribute to reduced tissue integrity and function. Collagen supplementation has therefore been investigated as a nutritional strategy to support tissue health in middle-aged and older adults. Aims This narrative review aimed to summarise current evidence on the physiological role of collagen, age-related changes in collagen metabolism, and the effects and safety of collagen supplementation in middle-aged and older adults. Materials and Methods PubMed, MEDLINE, and Google Scholar were searched for English-language publications published primarily between January 2010 and May 2026. Selected earlier studies were included to provide relevant mechanistic background. Systematic reviews, randomised controlled trials, cohort studies, observational studies, case series, and experimental studies supporting biological plausibility were considered. Results The most consistent clinical findings concerned selected skin outcomes, including modest improvements in hydration, elasticity, dermal density, and wrinkle appearance. Collagen supplementation was also associated with improvements in some musculoskeletal outcomes, particularly osteoarthritis-related pain, although several studies evaluated collagen together with exercise or other nutritional interventions. Evidence regarding obesity, glucose and lipid metabolism, arterial stiffness, and other cardiovascular outcomes was limited and inconsistent. Collagen supplementation was generally well tolerated, but most studies were short-term and long-term safety was rarely assessed. Conclusions Collagen supplementation may provide modest benefits for selected skin and musculoskeletal outcomes, but the magnitude, consistency, durability, and clinical relevance of these effects remain uncertain. Current evidence does not support specific clinical recommendations for metabolic or cardiovascular conditions. Large-scale, long-term randomised controlled trials using well-characterised collagen preparations and clinically relevant outcomes are required.